MULTICULTURAL DAâWA IN SCHOOLS FROM A SOCIOLOGICAL PERSPECTIVE - Dwiningrum, Siti Irene Astuti (WALISONGO, 2014)
AbstractMulticultural daâwa for the sake of building the paradigm of multicultural educationis not an easy work due to the determinants in social structure like social, cultural,economic and political determinants. The implementation of multicultural educationrelated to various social elements in society which are not in synergy one another.This article will reveal multicultural preaching carried out in schools and look at thestrategies of multicultural education is implemented in schools. Applying qualitativestudy by describing the initial data associated with a multicultural dakwah activity atthe three high schools in Yogyakarta Indonesia, this research concluded that multiculturaldaâwa in schools is a combination of several approaches namely the contributionapproach, the additive approach, the transformation approach, and the socialaction approach. Multicultural daâwa can help students to develop a social identitythat to be achieved based on the values of justice, equality and respect the diversity.The strategy developed by the school for implementing multicultural dakwah is bydeveloping language skills, language classes, art performance, the use of culturalsymbols, student exchange between tribes or between countries, and uniformity.***Dakwah multikultural untuk membangun paradigma pendidikan multikulturaltidak mudah karena struktur masyarakat memiliki diterminan sosial, budaya,ekonomi dan politik. Pelaksanaan pendidikan multikultural terkait dengan berbagaiunsur sosial dalam masyarakat yang satu dengan yang lain belum sinergis. Paparanini akan mengungkap dakwah multikultural yang dilaksanakan di sekolah dan melihatstrategi pendidikan multikultural dilaksanakan di sekolah. Melalui penelitiankualitatif dengan menggambarkan data awal terkait dengan aktivitas dakwahmultikultural pada tiga SMA di Yogyakarta, Daerah Istimewa Yogyakarta, Indonesia.Penelitian ini berkesimpulan dakwah multikultural di sekolah merupakan kombinasidari beberapa pendekatan yakni pendekatan kontribusi, pendekatan aditif,pendekatan transformasi, dan pendekatan aksi sosial. Dengan dakwah multikulturaldapat membantu siswa untuk mengembangkan identitas sosial yang hendakdicapainya berdasarkan nilai-nilai keadilan, kesetaraan dan menghargai perbedaan.Adapun strategi yang dikembangkan oleh sekolah untuk melaksanakan dakwahmultikultural adalah dengan cara mengembangkan kemampuan berbahasa, kelasbahasa, perfomance seni, penggunaan simbol budaya, pertukaran pelajar antar sukuatau antar negara, unifomitas.Keywords: multicultural daâwa, education, strategy, social identity